Urgensi Evolusi Bank di Era Digital - Zuchroh, Imama; Rina Irawati (Universitas Katolik Widya Karya Malang, 2025)
This research examines the fundamental transformation in Indonesia's banking industry triggered by Industry 4.0, specifically focusing on the evolution from traditional banking models to new-age banks. The study analyzes how disruptive technologies such as artificial intelligence, cloud computing, blockchain, and biometrics catalyze changes in banking digital capabilities and business models. Using a qualitative approach through comprehensive literature analysis and multiple case studies, this research identifies that digital transformation not only changes how banks operate but also fundamentally alters their value proposition to customers. The findings indicate that new-age banks are characterized by more agile organizational structures, advanced digital capabilities, and open platform-based business models that enable seamless integration with the broader digital ecosystem. This research contributes significantly to understanding the future of banking in the digital era and its implications for Indonesia's financial industry.